2008
DOI: 10.1590/s1413-86702008000100015
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of etiological diagnosis of nosocomial pneumonia

Abstract: Nosocomial pneumonia is a common complication in patients on mechanical ventilation and results in significant mortality. Diagnosis of pneumonia in patients who are intubated and under mechanical ventilation is difficult, even with the aid of clinical, laboratorial, and endoscopic tests. The objective of this study was to compare three methods of tracheal sputum collection in patients with a clinical and radiological diagnosis of pneumonia. Twenty-two patients with a clinical diagnosis of liver disease were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
(46 reference statements)
0
7
0
1
Order By: Relevance
“…As expected, all papers suffered from bias in their accuracy estimates of the index test from the use of an imperfect reference standard comparison, a well-known issue with comparative diagnostic accuracy studies [ 84 ]. The results of the quality assessment reviews conducted using the form adopted from CASP diagnostic study checklist showed that five papers [ 51 , 54 , 57 , 62 , 82 ] suffered from verification bias: not all patients received testing by both the index and the reference standard. In 38 papers [ 41 – 47 , 49 53 , 55 59 , 61 – 68 , 70 , 71 , 73 82 ], the results of the index test could have been influenced by the reference standard result.…”
Section: Resultsmentioning
confidence: 99%
“…As expected, all papers suffered from bias in their accuracy estimates of the index test from the use of an imperfect reference standard comparison, a well-known issue with comparative diagnostic accuracy studies [ 84 ]. The results of the quality assessment reviews conducted using the form adopted from CASP diagnostic study checklist showed that five papers [ 51 , 54 , 57 , 62 , 82 ] suffered from verification bias: not all patients received testing by both the index and the reference standard. In 38 papers [ 41 – 47 , 49 53 , 55 59 , 61 – 68 , 70 , 71 , 73 82 ], the results of the index test could have been influenced by the reference standard result.…”
Section: Resultsmentioning
confidence: 99%
“…Polymicrobial organisms also have been predominantly reported in neonatal VAP. (12) Moreover, Carvalho et al [16] concluded that the etiological diagnosis of VAP was considered as definitive when any microorganism was isolated from tracheal aspirates at concentrations of greater than or equal to103 cfu ml-1.…”
Section: Radiological Signsmentioning
confidence: 99%
“…The diagnosis of VAP was con rmed based on increased levels of serum C-reactive protein, presence of intracellular bacteria on gram-stained smears, or both. The etiological diagnosis of VAP was considered de nitive when any microorganism was isolated from tracheal aspirates at concentrations of ≥ 10 3 cfu mL − 1 [4]. To obtain a diagnosis, after performing Gram staining using tracheal aspirates collected at the onset of VAP, we sent the tracheal aspirate samples to the laboratory for the identi cation of causative bacteria.…”
Section: Sputum Studiesmentioning
confidence: 99%